(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2019)
This research project explored teachers’ beliefs of violence prevention approaches and self-efficacy. Relevant research indicates the value of violence prevention and conflict resolution education as well as the importance of teacher support of such programs. Theories of decision-making and self-efficacy provide the foundation for the variables that were examined through use of a survey instrument developed by Dr. K. King and Dr. T. Kandakai. Participants were sampled from two Florida school districts. Independent variables included teacher background and experience indicators including demographics and teaching/training experience. Dependent variables were comprised of multiple indicators of outcome value, efficacy expectation, and outcome expectation. MANOVAs and ANOVAs were utilized to identify relationships between the independent and dependent variables. Among the statistically significant findings a theme emerged: training history including variety of training, specific topics, and the interaction effects of combinations of training impacted perceptions of self-efficacy and outcome expectation more significantly than other demographic and background characteristics. The results suggest that the provision of a variety of training for teachers may benefit violence prevention practice by increasing perceptions of efficacy which may lead to an increase in consistent and effective utilization of various conflict resolution education programs and strategies.